Relacoes entre parâmetros antropométricos gerais e dimensões específicas da mao na preensão manual de atletas de alto rendimento de judô - Andrade Paz, G.; de Freitas Maia, M.; dos Santos Santiago, F. L.; Pinheiro Lima, V. (Brazilian Journal of Biomotricity, 2012)
The purpose of this study was to investigate the correlation among general anthropometric parameters (GAP)and hand-specific dimensions (HD)on the levels of maximum isometric handgrip(Fmax) in high-performance athletes of Judo. In total,15men and15 women competitors in judo at the national level participated this study. To verify the GAP were measured body mass, height and calculated the body mass index. In the HD were measured 5 lengths, 5 perimeters and 5 fingers spanof the dominant hand. The statistical analysis was developed through the mean and standard deviation followed by thelinear correlation coefficient of Pearson (r) being adopted value of p<0.05. In summary, there was moderate positive correlation between Fmax and height (r=0.63),and, between Fmaxand total body mass(r=0.70)for men,however, for the others variables the correlation levels were negligible or null. On the women group, there was moderate positive correlation between Fmax and height (r=0.64), although, the correlation levels were negligible or null for the others variables.Thus, GAP determined the Fmax more accurately than did HD. Thus, fingers are the smallest parts of the motor apparatus and their control is especially important for the accuracy of different techniques. Therefore, it is suggested in future studies to correlate anthropometric parameters betweenj udokas of different characteristics to generate evidence, which may be useful in training prescription.